2016
DOI: 10.3390/ijms17081259
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Derived Extracellular Matrix Induces Chondrogenic Differentiation in Human Adipose-Derived Mesenchymal Stromal/Stem Cells in Vitro

Abstract: Mesenchymal stromal/stem cells (MSCs) represent an area being intensively researched for tissue engineering and regenerative medicine applications. MSCs may provide the opportunity to treat diseases and injuries that currently have limited therapeutic options, as well as enhance present strategies for tissue repair. The cellular environment has a significant role in cellular development and differentiation through cell–matrix interactions. The aim of this study was to investigate the behavior of adipose-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 60 publications
3
88
0
Order By: Relevance
“…The scaffolds showed an ability to provide a suitable environment for human adipose-derived stem cells' survival and chondrogenesis. Another finding also supported by the studies that showed cartilage tissue formation when the AdSCs mixed with fibrin glue [25], as well as seeded in PRP-derived scaffold [23] or fibroblastderived extracellular matrix [26]. This result confirms the scaffold resulted in this study has good biocompatibility to the AdSCs and were suitable to be used in cartilage tissue engineering.…”
Section: ) Contact Angle and Water Uptakessupporting
confidence: 83%
“…The scaffolds showed an ability to provide a suitable environment for human adipose-derived stem cells' survival and chondrogenesis. Another finding also supported by the studies that showed cartilage tissue formation when the AdSCs mixed with fibrin glue [25], as well as seeded in PRP-derived scaffold [23] or fibroblastderived extracellular matrix [26]. This result confirms the scaffold resulted in this study has good biocompatibility to the AdSCs and were suitable to be used in cartilage tissue engineering.…”
Section: ) Contact Angle and Water Uptakessupporting
confidence: 83%
“…The human dECM bioink induced high cell viability over a period of time and also induced the expression of several adipogenic proteins with no supplementation of adipogenic factors [86]. Overall, human adipose tissue can be a source of dECM bioinks and also stem cells [1,86,90,91]. Rat and goat tissue and organs such as adipose tissue, heart and liver are additional sources of dECM bioinks [92][93][94].…”
Section: Decellularized Ecm As Bioinkmentioning
confidence: 99%
“…Tissue-and organ-derived dECMs also present problems when it comes to large scale in vitro analysis, something that is possible with cell-derived dECMs. Thus, in some instances, cell derived ECMs may be better than tissue or organ derived ECMs [1,91,123]. When cells are cultured, they synthesize, secrete and assemble ECM components around them.…”
Section: Cell-derived Ecms Versus Tissue/organ-derived Ecmsmentioning
confidence: 99%
See 2 more Smart Citations